Motyw zwierzęcy w twórczości językowej dzieci - Anna Wasilewska (Problemy Wczesnej Edukacji)
The subject of my research is the texts of children, which are a form of expressing imagination, so that it is possible to find in them references to real experiences and to images of the subconscious. For the isolation of creative strategies and describing the content of the images created by children I use a cognitive-linguistic perspective, and I refer to concepts of psychoanalysis. An animal theme is used by child authors the same way as in a fairy tale – as an allegory of social situations or as a vivid symbol of ambivalent feelings and difficult experiences, just as it is in fairy tales. An analysis of the linguistic creativity of children discovers a process of crystallisation of meanings in the mind, and ways of expressing them.